Komposisi, Sifat Fisik dan Tingkat Kesukaan Nasi Ungu - Agustina Souripet (Universitas Pattimura, 2015)
The aim of this research was to analyze the composition and physico-chemical properties of purple rice that is preferred by group of people in Bali. Purple rice were made with various pasta proportions, which were 100, 200, 300, 400 and 500 g were added to 700 g of rice. Physical properties include texture and color of purple rice with various proportion of pasta were analyzed followed by hedonic test. Parameters observed were, texture, color, and overall preference of purple rice. This research was designed as completely randomized design with 2 replicates and data of the results were analyzed using ANOVA at the significance level of 95%, followed by Duncan’s Multiple Range Test, if there was a significant difference. The results of research indicated that purple rice had texture of 2,19–2,37 N, with lightness of 42,7–54,97, tending to be blueish red (purple) with degree of redness of +8,33 until +15,13 and blueness degree of +1 until +4,60. Purple rice made from a mixture of ratio of 100 g rice: 300 g was preferred by panelists with texture of 2,26 N, lightness of 48,93, tending to be blueish red (purple) with degree value redness of +14,40 and blueness degree of +2,37.